2018
DOI: 10.22271/chemi.2018.v6.i4ai.05
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of washing treatment for extending the post-harvest shelf-life of papaya (Carica papaya)

Abstract: Papaya is most commonly grown fruits crop in tropical regions of world. About 25% -40% of postproduction losses of papaya can be observed specially in developing countries. Considerable amount of post-harvest losses of papaya is occurred due to un-hygienic conditions during post-production operations. Fruits hygiene condition is very important in order to extend its post-harvest self-life. Further, cleaning and washing practices are also very important in order to improve hygienic condition of product and dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Therefore, fruits and vegetables harvesting need to consider correct maturity based on subsequent post-harvest process and transport requirement. 15,19 Fruits can be divided into two groups based on their ripening behavior upon harvesting. Those not able to continue proper ripening process once removed from the plant (such as cherry, citrus fruits, grape, pineapple and pomegranate), and those able to continue ripening process off the plant (eg.…”
Section: Harvesting At Correct Maturitymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, fruits and vegetables harvesting need to consider correct maturity based on subsequent post-harvest process and transport requirement. 15,19 Fruits can be divided into two groups based on their ripening behavior upon harvesting. Those not able to continue proper ripening process once removed from the plant (such as cherry, citrus fruits, grape, pineapple and pomegranate), and those able to continue ripening process off the plant (eg.…”
Section: Harvesting At Correct Maturitymentioning
confidence: 99%
“…However, depending on the type of produce, some cold chain steps/operations may not be essential. Yet careful handling of the produce, suitably control of temperature and humidity in storages are an essential part of the process to minimize losses [3][4][5][6]15,16. Some of the steps in the Fig3are discussed in subsequent sections.…”
mentioning
confidence: 99%
“…The recent studies revealed that papaya post-production losses are between 25%-40%, particularly in developing countries (Gunathilake et al, 2018). Mechanical damages during harvesting, transportation, and post-harvest diseases cause significant loss of papaya fruits.…”
Section: Introductionmentioning
confidence: 99%
“…The most common fungal disease of papaya fruit is anthracnose, which is caused by Colletotrichum spp. and can result in 30–50% postharvest losses ( Gunathilake et al, 2018 ). Several technologies have been used to extend the postharvest shelf life of fruit, including fungicides, low-temperature storage, thermal processing, diverse packaging conditions, and preserving compounds obtained from natural sources that are “generally recognized as safe” ( Droby and Wisniewski, 2018 ).…”
Section: Introductionmentioning
confidence: 99%